EXAMINING EFFECTIVENESS OF MANAGEMENT CONTROL SYSTEM WITHIN INDONESIAN ANTI-CORRUPTION AGENCY: A LEVERS OF CONTROL PERSPECTIVE - Amelia, Lia; Hartanti, Dwi (LPPM STIE Muhammadiah Bandung, 2023)
his study aims to evaluate the effectiveness of the Management Control System (MCS) in mitigating dysfunctional behavior within Institution X, an Indonesian Anti-Corruption Agency. Drawing on the Levers of Control (LoC) theory, specifically emphasizing belief and boundary systems, the research investigates how the MCS effectively addresses and mitigates dysfunctional behavior that hampers organizational performance. Primary data were collected through a questionnaire administered to 34 budget users at the work unit level. Rigorous paper-check analysis and data triangulation, including interviews with specialists and Echelon III officials, were conducted to ensure the validity of the findings. The results highlight a noticeable divergence in perception between budget users and management regarding the effectiveness of the MCS. While budget users perceive the MCS as effective, management expresses concern about its ability to address dysfunctional behavior adequately. Additionally, the study reveals a recurring pattern of year-end spending spikes (YESS) over the past five years, indicating a potential correlation between myopic behavior and suboptimal planning. Blurred strategic boundaries within Institution X also contribute to dysfunctional behavior. These findings underscore the need to enhance the MCS's effectiveness in mitigating dysfunctional behavior and optimizing organizational performance. Based on the empirical evidence, it can be concluded that the current state of the MCS in Institution X meets basic user requirements but falls short of mitigating dysfunctional behavior and supporting management in achieving organizational goals. This study sheds light on the challenges associated with the MCS's effectiveness and provides actionable insights for enhancing management control systems within similar contexts